MENYELAMATKAN IDENTITAS SOSIAL DAN BUDAYA: STUDI KOMUNIKASI LINGKUNGAN DI WILAYAH RAWAN BANJIR BANTARAN SUNGAI CITARUM KABUPATEN BANDUNG - Erna Suminar (UKRI, 2026)
In Bale Endah District, Bandung Regency, perceptions of flooding are influenced by government information about relocation and the social and cultural identity of the local river basin community. Every rainy season, the community is aware of the danger of flooding that threatens their property and lives, but they are reluctant to move from the environment in which they live. This study aims to analyze the community's interpretation of government information and their attitude towards these appeals. Qualitative research using case studies was conducted to analyze the community's perceptions of relocation and government appeals in dealing with flooding. Data were collected through semi-structured in-depth interviews, observations, and literature reviews. The results of the study show that the rejection of relocation is due to emotional attachment to the place as part of their social and cultural identity. They view the place as part of their lives and livelihoods. Floods are a fate they must face despite the government's ongoing efforts to address the issue. The findings of this study suggest that effective communication requires the integration of social and cultural identity as a communication strategy in environmental messages.